2019
DOI: 10.1155/2019/7326590
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimization of Culture Conditions for Protein Production by a Newly Isolated Morchella fluvialis

Abstract: Morchella fungi are considered a good source of protein. The ITS region was used to identify Morchella isolated in the northern region of Iran. The isolated fungus was very similar to Morchella fluvialis. M. fluvialis was first isolated in Iran. Dried biomass of M. fluvialis contained 9% lipids and 50% polysaccharides. Fatty acid profiles of lipids of M. fluvialis are mainly made up of linoleic acid (C18:2) (62%), followed by palmitic acid (C16:0) (12%). Testosterone (TS) was also detected (0.732 ng/dry weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…39 In another study, concerning cultivation of Morchella fluvialis for optimization of protein production, it has been concluded that the use of a glucose-medium could lead to a biomass with high protein content. 45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In another study, concerning cultivation of Morchella fluvialis for optimization of protein production, it has been concluded that the use of a glucose-medium could lead to a biomass with high protein content. 45…”
Section: Resultsmentioning
confidence: 99%
“…A study on submerged cultivation of Morchella fluvialis in media containing different nitrogen sources confirmed that organic nitrogen sources seem to favor protein production compared to inorganic ones with yeast extract leading to a biomass of higher protein content compared to ammonium nitrate and urea. 45…”
Section: Resultsmentioning
confidence: 99%
“…P. sapidus excelled in the screening and produced biomass containing 21% true protein, 4% lipids, and 115 µg/g vitamin D 2 in 4 days [24]. Making use of statistical optimization, Morchella fluvialis mycelium with 38% w/w protein content was produced in liquid culture, deeming it a promising source of essential amino acids for the human diet [122]. Pleurotus species cultivated on agro-industrial by-products produced a total of 22 free amino acids in quantities up to 130.12 mg/g dw plus the neurotransmitter GABA and ornithine [123].…”
Section: Proteins and Peptidesmentioning
confidence: 99%
“…The crude protein contents of H. leucopus and other mushrooms were determined following the Chinese standard GB 5009.5-2016 (Standards China, 2016) by the Kjeldahl method using an automatic Kjeltec nitrogen analyser (Kjeltec TM 8400, FOSS, Denmark). Their amino acid compositions were determined by ion exchange chromatography with post-column derivatisation (with ninhydrin) using a high-speed amino acid analyser (LA8080, Hitachi, Japan) (Rahgo et al, 2019).…”
Section: Sample Analysismentioning
confidence: 99%